2011
DOI: 10.1038/jhh.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between circulating endothelin-1, soluble fms-like tyrosine kinase-1 and soluble endoglin in preeclampsia

Abstract: Placental overproduction of anti-angiogenic soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng) has a key role in the development of preeclampsia (PE). Circulating endothelin-1 (ET-1) levels are also elevated in PE. In this study, we investigated the correlation between ET-1 and sFlt-1, placental growth factor (PlGF), sEng levels during uncomplicated normotensive pregnancy and PE. A total of 218 pregnant primigravid women were enrolled: 110 with PE and 108 uncomplicated normotensive pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 32 publications
6
65
0
4
Order By: Relevance
“…Levels of sFlt1 and sEng both correlated with mean arterial pressure (data not shown) similar to previous studies. 32 When diastolic function was calculated using the definition used by Melchiorre et al, 19 we found significant higher sFlt1 and sEng levels and a worse GLS in the pathological group defined as lateral E′ <14 cm/s (all P<0.001).…”
Section: Correlation Between Angiogenic Factors and Echocardiography mentioning
confidence: 61%
“…Levels of sFlt1 and sEng both correlated with mean arterial pressure (data not shown) similar to previous studies. 32 When diastolic function was calculated using the definition used by Melchiorre et al, 19 we found significant higher sFlt1 and sEng levels and a worse GLS in the pathological group defined as lateral E′ <14 cm/s (all P<0.001).…”
Section: Correlation Between Angiogenic Factors and Echocardiography mentioning
confidence: 61%
“…In recent studies, this activation of the ET-1 system in preeclamptic or in HELLP syndrome pregnancies has been confirmed by different research groups [1 && , 3,4], and, most interestingly, this elevation of circulating ET-1 levels in preeclampsia has been shown to be closely related to the increased sFlt-1 levels in this syndrome [1 && ,3]. Activation of the endothelin system has repeatedly been reported in clinical preeclampsia, and also in different experimental preeclampsia models.…”
Section: Elevated Endothelin In Preeclampsiamentioning
confidence: 67%
“…This result was in agreement with other animal and human studies that reported a high correlation between sENG and sFlt-1 on one hand and disease severity on the other hand. 26,27 A causal relationship between these antiangiogenic growth factors and fetal mortality in PE is strongly suggested by the observed negative correlation between sENG/sFlt-1 and the number of live pups and their birth weight (Figure 1c and d, Figure 2a-c) and the direct correlation between sENG and the number of dead pups (Figure 2d).…”
Section: Discussionmentioning
confidence: 94%